Occult hepatitis B infections among blood donors in Lao PDR. Issue 1 (12th August 2013) - Jutavijittum, P.; Andernach, I. E.; Yousukh, A.; Samountry, B.; Samountry, K.; Thammavong, T.; Keokhamphue, J.; Toriyama, K.; Muller, C. P.
<x xml:space="preserve">Abstract</x> Background and Objectives In Lao People's Democratic Republic, hepatitis B virus is highly endemic. However, blood donations are only screened for HBsAg, leaving a risk of transmission by HBsAg‐negative occult infected donors. Here, we characterized first‐time blood donors to assess prevalence of hepatitis B virus infections and occult infected donors. Materials and Methods Sera were screened for HBsAg, HBeAg and anti‐HBs, anti‐HBc and anti‐HBe antibodies. Occult HBV infections (OBIs) were assessed in HBsAg‐negative sera by PCR, and sera of HBsAg positive and occult infected donors were phylogenetically characterized. Results 9·6% of the donors were HBsAg positive, and 45.5% were positive for at least one of the hepatitis B virus serum markers. More than 40% HBsAg carriers were HBeAg positive, with HBeAg seroconversion occurring around 30 years of age. Furthermore, 10·9% of HBsAg‐negative, anti‐HBc and/or anti‐HBs‐positive donors were occult infected with hepatitis B virus. Thus, at least 3·9% of blood donations would potentially be unsafe, but hepatitis B virus DNA copy numbers greatly varied between donors. Conclusion In Lao People's Democratic Republic, a sizable proportion of HBsAg‐negative and anti‐HBc antibody‐positive blood donations are potentially DNA positive and infective for hepatitis B.